Macroeconomics and the real world - Backhouse, Roger, 1951-; Salanti, Andrea, 1950- (Oxford ; New York : Oxford University Press, 2000)
This book covers the use of evidence to understand the business cycle, the operation of monetary policy, and economic growth.
v. 1. Econometric techniques and macroeconomics. -- v. 2. Keynesian economics, unemployment, and policy.
Includes bibliographical references and index.
gau 29/01/14, uaj 17/04/2015
Loans
Keywords: Macroeconomics; Econometrics; Keynesian economics